MULTIPLE SCLEROSIS AND PREGNANCY: A SYSTEMATIC LITERATURE REVIEW (2018–2026) - Weronika Szymacha; Karol Józef Szkarłat; Maksymilian Szklarski; Jędrzej Sztajura; Szymon Targosz; Michał Stachel; Ewa Maraszewska; Aleksandra Płecka; Karol Zimnicki; Alicja Stępień (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and purpose: Multiple sclerosis (MS) predominantly affects women of reproductive age, necessitating a delicate balance between maternal disease control and fetal safety. This review aims to synthesize contemporary evidence regarding therapeutic management during pregnancy, labor, and the puerperium to optimize clinical outcomes. Description of the state of knowledge: Pregnancy induces systemic immunomodulation (Th2-shift), reducing annualized relapse rates (ARR) by 70–80% in the third trimester. Current evidence indicates that MS does not adversely impact fertility or obstetric outcomes. Landmark data on ocrelizumab (N=3244) confirm that peri-conceptional exposure does not correlate with increased congenital malformations. Conversely, the "rebound effect" remains a significant risk following the cessation of high-efficacy therapies (HET) such as natalizumab. Pharmacokinetic analyses support the safety of breastfeeding under monoclonal antibody coverage, as the Relative Infant Dose (RID) for most agents remains below 1%, well within the 10% safety threshold. Conclusions: MS management must transition from mandatory drug discontinuation to personalized risk stratification. A shared decision-making model involving neurologists, obstetricians, and patients is essential. Future research should prioritize long-term neurodevelopmental data for infants exposed to novel biological therapies.